The Amelioration of Detrimental Biochemical Anomalies by Supplementing B, C, and E Vitamins in Subjects with Type 2 Diabetes Mellitus May Reduce the Rate of Development of Diabetic Retinopathy - Subhasish Pramanik; Kaustav Banerjee; Lakshmi Kanta Mondal (Journal of Diabetes Research)
Excessive intracellular glucose in insulin-independent tissues including nerve, nephron, lens, and retina invites mishandling of metabolism of glucose resulting in a background of increased oxidative stress, advanced glycation end products (AGE) formation, lipid peroxidation, and failure of antioxidant defense systems in type 2 diabetes mellitus (T2DM). All these detrimental biochemical anomalies ultimately attack biological membranes and especially capillary beds of the retina, resulting in the breakdown of the inner blood-retinal barrier and the initiation of diabetic retinopathy (DR). If these disarrays are corrected to a large extent, the development of DR can be avoided or delayed. In this prospective clinical trial, 185 patients with T2DM who received B vitamins, vitamin C, and vitamin E along with antidiabetic medication for five years demonstrated a slower rate of the development of DR and reduced abnormal biochemical mediators like reactive oxygen species (ROS), malondialdehyde (MDA), AGE, and vascular endothelial growth factor (VEGF) compared to 175 T2DM individuals who were treated with only antihyperglycemic drugs.